Multi-dimensional effects of financial development and technological innovation on green growth in China - Cao, Jianhong (2022)
This study firstly examines the impact of financial development and technological innovation on green growth from three technical dimensions, using a sample set from 30 Chinese provinces from 2011 to 2018. Finally, this study explores and analyzes the dredging impact of the combination of financial development and technical innovation on the front and rear ends of the green growth route based on technological progress and floating population. The findings of the first objective show that the weakness of financial institutions destroys the original "dissipative structure" formed via comprehensive level of financial development and comprehensive level of technological innovation, which leads to the misallocation between the two subsystems, and this disharmony weakens the synergetic development and ultimately slows down or even degrades the evolution of the self-organizing system. When financial development exceeds a certain proportion of technological innovation, it will aggravate financial "vanishing effect". However, financial system innovation can not completely offset the harmful influence of financial overdevelopment on green growth. The empirical results of the second objective revealed that the local financial institutions' scale expansion significantly dampened green growth for the local area, while the effect is facilitated in the surrounding area. Local stock market size has a substantial beneficial role in green growth both in local and neighboring areas. Local technological innovation significantly boosts local green growth, but not significantly to surrounding areas. The adverse impact on green growth is exacerbated by the interaction between financial development and technological innovation. The results of the third objective indicated that the development of the financial institution scale will strongly contribute to green growth volatility. An increase in the stock market scale also can significantly contribute to green growth volatility. Besides, the synergies (interactions) between financial development and technological innovation can significantly moderate green growth volatility. Furthermore, financial development which is captured by the stock market indicator is shown to be substantially higher efficient in dampening green growth volatility than financial development covered by the financial institutions indicator. The fourth objective of the study indicate that the association between green growth (GG) and floating population (FP) is nonlinear when digital financial inclusion is the threshold variable. To considerably increase green growth, output-biased technological progress needs more assistance from digital financial inclusion than input-biased technology innovation. From the point of view of "digitization + financial scale + inclusion", digital financial inclusion not only boosts the positive effect that technological innovation has on green growth, but also helps to reduce the adverse effect that green growth has on floating populations. This study has important reference significance for replacing old growth drivers with new ones, industrial structure upgrading, development model transformation and superior economic development at the present stage and offers a fresh theoretical foundation for promoting the sustainability, balance and stability of China's green growth.